Are Black Offenders Disproportionately Victimizing Asian Americans During the COVID-19 Pandemic? Comparison to Expected Racial Distributions and the Pre-Pandemic Period - Roberts, Aki (Victims & offenders, 2025)
During the COVID-19 pandemic, reports of violence against Asian Americans surged in traditional and social media, often depicting an Asian victim attacked by a Black assailant and suggesting heightened Black animosity toward Asian Americans. Scholars have challenged this Black-Asian conflict narrative by highlighting that White perpetrators commit over 75% of anti-Asian hate crimes. However, the large share of White offenders in anti-Asian hate crime may simply reflect American racial demographics, and Black offenders could be disproportionately victimizing Asian Americans relative to the size of the Black population or offender pool. The current study examined the share of Black offenders in violence against Asian victims relative to the racial composition of local populations or offender pools. Analysis using 2020 NIBRS and Census data indicated overrepresentation of Black offenders in violence against Asian victims relative to the weighted average of the Black population proportion of the 351 cities in which such incidents occurred. However, Black offenders’ share of violence against Asian victims closely matched the proportion Black in the average local potential offender pool. Comparison of 2019 and 2020 data indicated an increase in Black offenders’ share of violence against Asian victims, but this difference in the distributions was not statistically significant.